Question
\( 1.1 .4 \quad 3 ^ { x + 3 } - 3 ^ { x + 2 } = 486 \)
Ask by Hanson Frazier. in South Africa
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( x = 3 \)
Solution
Certainly! Let's solve the equation step by step:
\[
3^{x + 3} - 3^{x + 2} = 486
\]
### Step 1: Factor Out the Common Term
Notice that both terms on the left side of the equation have a common factor of \( 3^{x + 2} \). We can factor this out:
\[
3^{x + 3} - 3^{x + 2} = 3^{x + 2} \cdot 3^1 - 3^{x + 2} = 3^{x + 2} (3 - 1) = 3^{x + 2} \cdot 2
\]
So, the equation becomes:
\[
3^{x + 2} \cdot 2 = 486
\]
### Step 2: Isolate the Exponential Term
Divide both sides of the equation by 2 to isolate \( 3^{x + 2} \):
\[
3^{x + 2} = \frac{486}{2} = 243
\]
### Step 3: Express 243 as a Power of 3
We know that:
\[
243 = 3^5
\]
So, the equation now is:
\[
3^{x + 2} = 3^5
\]
### Step 4: Set the Exponents Equal
Since the bases are the same and the equation \( 3^a = 3^b \) implies \( a = b \), we can set the exponents equal to each other:
\[
x + 2 = 5
\]
### Step 5: Solve for \( x \)
Subtract 2 from both sides:
\[
x = 5 - 2
\]
\[
x = 3
\]
### **Answer**
\( x = 3 \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
Let’s solve the given equation \( 3^{x+3} - 3^{x+2} = 486 \). We can factor out \( 3^{x+2} \): \[ 3^{x+2}(3 - 1) = 486 \] This simplifies to: \[ 3^{x+2} \cdot 2 = 486 \] Dividing both sides by 2 gives: \[ 3^{x+2} = 243 \] Since \( 243 = 3^5 \), we can equate the exponents: \[ x + 2 = 5 \] Solving for \( x \) gives: \[ x = 3 \] So, the solution is \( x = 3 \).